Formulation of chicks feed based on palm kernel cake (PKC) - Foong, Kah Kah (2008)
Poultry feed requirement increased rapidly due to growing populations in our nation. Thus it is critical to find out some alternatives ways to overcome the problems. Study was carried out in UMP to test the effects of chicks on different ratio of Palm Kernel Cake (PKC) based feed. Palm kernel cake identified as substitute protein for cattle feed and it is very potential use in poultry industry. However, the lacked of digestible protein might lead the limitations of it in poultry feed. The activities carried on included analysis of feed ingredients (PKC), to analyze final designed feed for chicks and evaluate the effects on chicks. Developed feed with sufficient of nutrients requirements and suitable PKC ratio are the big challenge to deal with in this study. The evaluations on chicks are to observe the effects of feeds on chicks. The study took 3 weeks to evaluate based on two type feed, feed A with 15% PKC and feed B with 20% PKC. From the analysis, the nutrition composition for both designed feed are fulfilled the standard requirements for poultry feed. From the observation and result, it shows that the performance of group A which is 906.3 g better than group B 899.2g in the end of research. Both feed are suitable to used as chicks feed, however based on economy factor, feed B is suitable for commercialize. The average food consumption for feed A is 62.06 g/day and feed B is 63.43 g/day. There are not significant relationship between food consumption and weight gain. This is because group B consumed more feed but their weight gain is lower. The feed / weight gain ratio for feed A is 1.4832 whereas feed B is 1.4814.